2017
DOI: 10.1061/(asce)ir.1943-4774.0001117
|View full text |Cite
|
Sign up to set email alerts
|

Crop Coefficient Curve for Paddy Rice from Residual Energy Balance Calculations

Abstract: The crop coefficient (K c) values of rice paddy are important for estimating accurate rice crop evapotranspiration (ET c), water transfers planning, efficient irrigation management, and hydrological studies. In this study, ET c was measured and a generalized K c curve was calculated for paddy rice in the Sacramento Valley, California. Field experiments were conducted in three rice paddy fields during the 2011-2013 growing seasons. Surface renewal analysis, after calibration using eddy covariance method, was ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Agriculture 2019, 9, x FOR PEER REVIEW 7 of 20 Figure 2 shows an example of the scatter of the H versus H' data obtained during the entire 2016 season in the non-saline orchard. Alpha calibrations were calculated separately for unstable conditions (upward fluxes), represented by positive H, and for stable conditions (downward fluxes), represented by negative H. It is well known that unstable conditions enhance turbulence with respect to stable ones, so separate calibration is common in literature [41,45,46].…”
Section: Orchard Station Id Type Of Et Stations Methods For Estimating Hmentioning
confidence: 99%
“…Agriculture 2019, 9, x FOR PEER REVIEW 7 of 20 Figure 2 shows an example of the scatter of the H versus H' data obtained during the entire 2016 season in the non-saline orchard. Alpha calibrations were calculated separately for unstable conditions (upward fluxes), represented by positive H, and for stable conditions (downward fluxes), represented by negative H. It is well known that unstable conditions enhance turbulence with respect to stable ones, so separate calibration is common in literature [41,45,46].…”
Section: Orchard Station Id Type Of Et Stations Methods For Estimating Hmentioning
confidence: 99%
“…The actual evapotranspiration (ET a ) was measured using the residual of energy balance (REB) method with a combination of surface renewal (SR) and eddy covariance (ECov) techniques. The SR and ECov are well-recognized methods to estimate the sensible heat flux density (H) and to calculate the latent heat flux density (LE), using the REB approach [23][24][25][26][27][28].…”
Section: Et Monitoring and Data Processingmentioning
confidence: 99%
“…The SR H and the ECov H were used to determine the LE values. The advantage from using both the ECov and SR methods was that they are independent and similar results provide a high level of confidence in the data used [26,28,29]. Latent heat flux density was calculated using the Residual of Energy Balance equation, as follows:…”
Section: Et Monitoring and Data Processingmentioning
confidence: 99%
“…Similar to "ETc-SR" at the initial stage, the "ETc-EC" was higher than "ETc-FAO", with "RMSE" of 0.88 mm/day and 18.68% "NRMSE", then the "ETc-EC" values become lower than the "ETc-FAO" during mid-season and lateseason growth stages, by "RMSE" values equal to 0.74 and 0.35 mm/day and "NRMSE" values equal to 13.82% and 7.33% for each season, respectively. Montazar et al (2017) explained the observed high values of the "ETc" determined by "REB" methods, at the beginning of the flooded rice season, as a result to the small canopy cover proportional to the water surface in the flooded field, that in this case the surface area of the water exposed to the weather conditions are higher than the area of the plants canopy, which produce higher "LE". As the size of rice canopy increases, it covers the water surface, and avoid the effect of the water surface in the "LE" values.…”
Section: Figure 3 Half-hourly "Lesr" Vs "Leec" For Rice and Wheat Crops As An Evaluation For "Sr" Calibration Process Crop Water Requiremmentioning
confidence: 93%